Interatomic Coulombic decay following Ne 1s Auger decay in NeAr - Ouchi, Toshihiko; Sakai, K.; Fukuzawa, H.; Higuchi, I.; Demekhin, Philipp V.; Chiang, Ying-Chih; Stoychev, Spas Dimitrov; Kuleff, Alexander I.; Mazza, T.; Schöffler, M.; Nagaya, K.; Yao, M.; et al. (Physical review. A, Atomic, molecular, and optical physics, 2011)
Using momentum-resolved electron-ion multicoincidence spectroscopy, we have investigated interatomic Coulombic decay (ICD) in the heteronuclear NeAr dimer following Ne 1s Auger decay. The measured intensity ratio for the three ICD transitions Ne2+(2s−12p−11P)Ar to Ne2+(2p−21S)-Ar+(3p−1), Ne2+(2s−12p−11P)Ar to Ne2+(2p−21D)-Ar+(3p−1), and Ne2+(2s−12p−13P)Ar to Ne2+(2p−23P)-Ar+(3p−1) reasonably agree with predictions. The kinetic energy release distribution for the fragmentation to Ne2+(2p−21D)-Ar+(3p−1) after the ICD transition from singlet Ne2+(2s−12p−11P)Ar state, which is a mirror image of the kinetic energy distribution of the emitted ICD electrons, suggests that the corresponding ICD rate is roughly two times lower than predicted by ab initio calculations.